Cover Picture: Phys. Status Solidi C 10/2013. Issue 10 (11th October 2013) - Chauveau, Jean‐Michel; Sallet, Vincent; Morhain, Christian; Feuillet, Guy
<x xml:space="preserve">Abstract</x> ZnO is a remarkable multifunctional material with a distinctive set of properties including a direct bandgap of ∼3.4 eV and an exciton binding energy of ∼60 meV. It also has a high transparency over the visible spectrum, a strong piezoelectric response, a very wide range of tuneable conductivities (varying from semi‐insulating to semimetallic) and good biocompatibility. Sandana et al. on pp. 1317–1321 report on the growth of self‐forming, vertically‐aligned arrays of black‐body‐like ZnO "moth‐eye" nanostructures on Si(111), c‐Al2O3, ZnO and high manganese austenitic steel substrates using pulsed laser deposition. Such "moth‐eye" nanostructures have a graded effective refractive index and exhibit black‐body characteristics. In photovoltaic applica‐tions they may, therefore, have potential for use as anti‐reflective coatings, light trapping layers and nanostructured template back‐electrodes. In LED applications they may have potential for use as coatings for enhancement of light extraction, as active ZnO layers for light emission or as nanostructured templates for (In)GaN regrowth. Moreover, since ZnO nanostructures can be grown readily on a wide range of substrates, it is suggested that such an approach could facilitate the growth of GaN‐based devices on mismatched and/or technologically important substrates, which may have been inaccessible till present. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>